The Relationship Between Family Social Support and Self-Efficacy on Flourishing in Malahayati University Students - -, Adinda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Students face various new demands in their lives, such as academic pressures and environmental demands. In their lives, students are often faced with various situations that impact their level of flourishing. Family social support and self-efficacy are factors that influence an individual's level of flourishing. Therefore, the purpose of this study was to determine the relationship between family social support and self-efficacy and flourishing in students. The sampling technique used was quota sampling. The subjects were 254 students at Malahayati University. The measurement instruments used were the PERMA Scale, the PSS-FA Scale, and the GSE Scale. The results showed that the level of flourishing in students at Malahayati University was in the moderate category. This may be due to students feeling that their lives were not yet good enough to achieve happiness and satisfaction. A significance value of 0.000 was obtained, with 0.000 < 0.05. This suggests that family social support and self-efficacy simultaneously have a relationship with flourishing. There is a positive relationship between peer social support and personality tendencies toward flourishing in college students.